Gender responsiveness of selected primary school english textbooks in Zimbabwe - Maruzani, Nyevero; Mutamba, Memory (David Publishing, 2019)
When classrooms are not gender responsive, boys and girls seating in the same classroom and learning from the same teacher receive very different education. Each and every textbook and all learning materials tell a story about people; how they relate to one another and to the environment within which they live. The present study is a desk research conducted to establish the extent of gender responsiveness of selected primary school English textbooks in Zimbabwe. Using the ABC of Gender Analysis framework, the study made quantitative and qualitative analyses of two selected series of primary school English textbooks, which are Step in New Primary English (Grade 1 to 7) and Ventures English Alive! (Grade 1 to 7 Pupil’s Book). Components of the ABC of Gender Analysis were used to make a critical analysis of the textbooks. Despite the fact that a number of measures have been put in place to address issues of gender inequality in all sectors, findings from the study revealed that the selected primary school English textbooks continue to perpetuate gender discrimination and bias. This impacts negatively on the education of girl children and it is detrimental to equal educational attainment for boys and girls. Girls tend to be affected and lag behind, others fail to excel and even drop out. The study recommends the promotion of zero tolerance to gender biases and stereotypes in all learning and teaching environments. The study also recommends that school textbooks be exposed to the rigour of gender analysis before they are recommended for use in any educational activity.